Pemanfaatan koleksi Perpustakaan Pusat Pendayagunaan Informatika dan Kawasan Strategis Nuklir BATAN menggunakan ISO 11620:2014 - Suhendani Suhendani (Universitas Padjadjaran, 2021)
The library collection is an essential element of a library. The increasing turnover and collection usage by users in the library will affect the library's performance. The availability of collections in the library is an adequate number of collections and the availability of several collections owned by a library. This study aimed to determine utilization of the Central Library for Utilization of Informatics collection and the BATAN Nuclear Strategic Area using ISO 11620:2014. This study used a descriptive method with a quantitative approach, derived from numerical data of circulation services from 2017 to 2019. Results showed that the overall level of borrowing library materials decreased due to reduced direct user visits to libraries and digital libraries. The utilization level of library collections by the population to be served has increased significantly. Documents downloaded were six titles, and the highest download frequency was four times in 2018. Besides, documents downloaded were four titles, and the highest download frequency was 23 times in 2019. Users found the information they were interested in from electronic collections that were downloaded every year, namely radiography training exam questions. The presence of electronic documents is considered quite relevant and useful according to the user's information needs. Many collections of the Central Library for the Utilization of Informatics and the Nuclear Strategic Area of BATAN are not lent due to the availability of collections that are not yet relevant to users' needs. It significantly affects the turnover of the collection.